2015
DOI: 10.3389/fmicb.2015.00479
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of Traditional Chinese Medicine monomers against Streptococcus pneumoniae via inhibiting pneumococcal histidine kinase (VicK)

Abstract: Two-component systems (TCSs) have the potential to be an effective target of the antimicrobials, and thus received much attention in recent years. VicK/VicR is one of TCSs in Streptococcus pneumoniae (S. pneumoniae), which is essential for pneumococcal survival. We have previously obtained several Traditional Chinese Medicine monomers using a computer-based screening. In this study, either alone or in combination with penicillin, their antimicrobial activities were evaluated based on in vivo and in vitro assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The results clearly indicate that the degree of the antibiofilm effect is positively correlated with the length of the alkyl chain in gallic acid esters, including lauryl gallate. Furthermore, in support of our findings, this type of suppressive activity, observed here in lauryl gallate, has also been noted by Zhang et al [37] against another biofilm-forming pathogen, Streptococcus pneumoniae. Values are presented as the mean ± standard error obtained from three independent experiments (n = 3-9).…”
Section: Antibacterial Activity Of C12-lg On S Mutanssupporting
confidence: 93%
“…The results clearly indicate that the degree of the antibiofilm effect is positively correlated with the length of the alkyl chain in gallic acid esters, including lauryl gallate. Furthermore, in support of our findings, this type of suppressive activity, observed here in lauryl gallate, has also been noted by Zhang et al [37] against another biofilm-forming pathogen, Streptococcus pneumoniae. Values are presented as the mean ± standard error obtained from three independent experiments (n = 3-9).…”
Section: Antibacterial Activity Of C12-lg On S Mutanssupporting
confidence: 93%
“…Therefore, TCSs may have potential to be effective targets of anti- S. mutans agents. Of note, some natural agents have been found to suppress TCSs in S. mutans (Zhang et al, 2015; Li et al, 2018), but no similar studies have been reported on black tea extracts or theaflavins. In the present study, based on RT-PCR results, we speculate that TF3 suppresses at least three TCSs in S. mutans (LytST, VicRK, and ComDE), which might explain its inhibitory effect on biofilm formation, acid tolerance and acid production.…”
Section: Discussionmentioning
confidence: 99%
“…These genes and their products are therefore potential new antimicrobial targets (Roemer and Boone, 2013 ; Scheffler et al, 2013 ). This knowledge is of utmost importance to the development of new screening platforms for identification and selection of compounds targeting specific essential genes based on protein interactions and mutant libraries (Zhang et al, 2015 ; Morita et al, 2016 ). A classical approach, applicable to select compounds that are able to interact with a specific target, is based on affinity chromatography systems.…”
Section: Genomics and Advances In Antibiotics Researchmentioning
confidence: 99%